Tumor‐suppressive roles of ΔNp63β‐miR‐205 axis in epithelial–mesenchymal transition of oral squamous cell carcinoma via targeting ZEB1 and ZEB2. Issue 10 (10th May 2018) - Hashiguchi, Yuma; Kawano, Shintaro; Goto, Yuichi; Yasuda, Kaori; Kaneko, Naoki; Sakamoto, Taiki; Matsubara, Ryota; Jinno, Teppei; Maruse, Yasuyuki; Tanaka, Hideaki; Morioka, Masahiko; Hattori, Taichi; et al.
Abstract : We previously revealed that epithelial‐to‐mesenchymal transition (EMT) was mediated by ΔNp63β, a splicing variant of ΔNp63, in oral squamous cell carcinoma (OSCC). Recent studies have highlighted the involvement of microRNA (miRNA) in EMT of cancer cells, though the mechanism remains unclear. To identify miRNAs responsible for ΔNp63β‐mediated EMT, miRNA microarray analyses were performed by ΔNp63β‐overexpression in OSCC cells; SQUU‐B, which lacks ΔNp63 expression and displays EMT phenotypes. miRNAs microarray analyses revealed miR‐205 was the most up‐regulated following ΔNp63β‐overexpression. In OSCC cells, miR‐205 expression was positively associated with ΔNp63 and negatively with zinc‐finger E‐box binding homeobox (ZEB) 1 and ZEB2, potential targets of miR‐205. miR‐205 overexpression by miR‐205 mimic transfection into SQUU‐B cells led to decreasing ZEB1, ZEB2, and mesenchymal markers, increasing epithelial markers, and reducing cell motilities, suggesting inhibition of EMT phenotype. Interestingly, the results opposite to this phenomenon were obtained by transfection of miR‐205 inhibitor into OSCC cells, which express ΔNp63 and miR‐205. Furthermore, target protector analyses revealed direct regulation by miR‐205 of ZEB1 and ZEB2 expression. These results showed tumor‐suppressive roles of ΔNp63β and miR‐205 by inhibiting EMT thorough modulating ZEB1 and ZEB2 expression in OSCC. Abstract : We previously revealed that epithelial‐to‐mesenchymal transition (EMT) was mediated by ΔNp63β, a splicing variant of ΔNp63, in oral squamous cell carcinoma (OSCC). In this study, to identify miRNAs responsible for ΔNp63β‐mediated EMT, miRNA microarray analysis was performed by ΔNp63β‐overexpression in OSCC cells. We focused on miR‐205 by comparing expression profiles of the two OSCC clones, and we present some evidences that miR‐205 is possibly involved in ΔNp63β‐mediated EMT.